Tradition and Modernity: Leadership struggle for political space in Warri South Local Government Area of Delta State, Nigeria - Okolie, Ugo Chuks; Mukoro, Akpomuvire (ARISTO, 2025)
This paper investigates the issue of incorporating traditional rulers into Nigeria's modern local government system with the goal of resolving issues that arise from the interface of tradition and modernity in Warri South Local Government Area of Delta State. This theoretical paper draws its arguments primarily from secondary sources of data, such as existing legal frameworks and other associated policies, journal publications, and textbooks. This paper shows how traditional leadership institutions strategically used decentralized governance policy reforms to reestablish themselves as the mainstay in grassroots politics. This review is placed within the framework of the debate over the worth of traditional leadership institutions, in the twin processes of democratic transformation and decentralized governance. While the opposing side of the debate dismisses them as mere impediments, the other contends that they are assets that can be used to effectively domesticate reforms, because traditional leaders exhibit ethical principles such as political transparency, accountability, and probity. While research finding showed that traditional leaders possess the capacity to play an advisory role in efforts to institutionalize and customize reforms to the necessities of the community but their poor material circumstances make them unanimously readily available targets for politicians intent on fulfilling their own intended political objectives. The paper thus recommended, among other things, that local government actors and traditional authorities in Warri South Local Government Area should see one another as partners in progress and foster mutual respect and understanding. They must be aware that they cannot function in a watertight compartment and should therefore be cooperative and tolerant.